PENGARUH ARANG AKTIF BAMBU TERHADAP KARAKTERISTIK PEMATANGAN DAN SIFAT MEKANIK KARET PEREDAM GONCANGAN KENDARAAN BERMOTOR - Bambang Sugiyono; Hari Adi Prasetya (Balai Riset dan Standardisasi Industri Palembang, 2018)
The research on the utilization of bamboo activated charcoal as a filler for sport damper has been done. This study aims to obtain the best formula of motor vehicle sport damper with bamboo activated charcoal filler and to examine the characteristics of the resulting sport damper. The design is Completely Randomized Design (RAL) non factorial, each treatment repeated three times, by treatment of B1 (activated charcoal concentration 20 phr), B2 (activated charcoal concentration 30 phr), B3 (activated charcoal concentration 40 phr ), B4 (activated charcoal concentration 50 phr) and B5 (activated charcoal concentration 60 phr). The parameters observed were characteristic of vulcanization of rubber compound sport damper, ie optimum vulcanization rate (t90), pravulcanisation time (ts2) and torsion modulus (ML and MH) and mechanical characteristics, ie tear resistance and compression set. The results showed that all treatments had a significant effect on the characteristics of vulcanization and mechanical characteristics of sport damper. The best treatment of motor vehicle sport damper obtained of B3, B4 and B5, with characteristics characteristic is fulfill of commercial sport damper. The bamboo activated charcoal can be used as a filler for rubber products and can be used as an alternative to commercial fillers.